Syntheses and structural properties of 1,8-diazacyclotetradeca-3,5,10,12-tetraynes - Hövermann, Kirstin; Ritter, Joachim; Rominger, Frank; Nuber, Bernhard; Gleiter, Rolf (European journal of organic chemistry, 2000)
The syntheses of 1,8-diazacyclotetradeca-3,5,10,12-tetrayne (2a), its N,N′-dimethyl (2b), N,N′-diethyl (2c), N,N′-diisopropyl (2d), N,N′-diallyl (2e), and N,N′-dibenzyl (2f) derivatives were achieved in a one-pot procedure from primary amines and 1,6-dibromo-2,4-hexadiyne (4). Diffraction studies on single crystals of 2c−2f reveal a chair conformation with the substituents in the diaxial positions. The preference of the axial orientation of the substituents on the nitrogens in 2c−2f is due to several contributions: minimal synaxial 1,3 interactions of the NR bond and the lone pair with adjacent CH and CC bonds.
Gesehen am 27.10.2020